Spray drying of shark liver oil pool: Effects on physical-chemical properties and antioxidant capacity - Caridad M. García; Mirna Fernández; Orestes D. López; Livan Delgado-Roche; Antonio Nogueira; Mirta Castiñeira; Esteban A. Medrano (GarVal Editorial Ltda., 2018)
Context: Spray-drying is a technique used to produce encapsulated products, thus improving the stability of components as well as their organoleptic characteristics. Aims: To evaluate the effect of microencapsulation of shark liver oil pool by spray drying on its physical-chemical properties and antioxidant capacity. Methods: A mix design was created with a constant load of oil, made possible by controlling the proportion between chitosan acetate and maltodextrin. Loss on drying, encapsulation efficiency and yield were determined for the microcapsules. Reversed-phase HPLC analysis was used in order to determine the vitamin A content in microencapsulated and non-microencapsulated oil, as well as its delivery from the dried product. Vitamin A was the active compound used as a chemical marker. The following parameters were also evaluated: organoleptic characteristics, moisture content, particle size, surface morphology and antioxidant capacity. Results: The encapsulation efficiency of microencapsulated oil increased slightly as the concentration of chitosan acetate increased. In order to achieve a greater encapsulation efficiency and a lower moisture content in microencapsulated oil, the proportion between chitosan acetate and maltodextrin should be maintained at 35% and 35% each, according to established manufacturing conditions. Both polymers prevent oil from leaving the droplet. This is a very important factor in storage stability of vitamins and fatty acids, which are subject to oxidative deterioration. Conclusions: Spray-drying microencapsulation of pool oil does not affect vitamin A content or delivery; fatty acid content and antioxidant capacity are also not affected.